The formation of meta-stable sodium sulphate heptahydrate during drying as studied by NMR - Saidov, Tamerlan; Pel, Leo (Diffusion Fundamentals, 2009)
Salt weathering is a major cause of deterioration of porous building materials. Of the salts responsible, especially sodium sulfate is seen as very damaging. However many questions arise concerning which sodium sulfate phase will crystallize out during salt weathering. In this study we focused on the crystallization during isothermal drying of a sample saturated with a sodium sulfate solution. As the material is drying moisture will leave and hence the salt concentration will rise until the maximum solubility is reached. From that point on crystals will be formed. Using NMR we have measured quasi simultaneously both the moisture and Na profiles during drying. These experiments have been performed at various temperatures and concentrations. In our NMR experiments we observe the formation of a metastable phase of sodium sulfate, the heptahydrate crystals.